2003
DOI: 10.1016/s0014-5793(03)00678-1
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin is much more effective than saturated phosphatidylcholine in excluding unsaturated phosphatidylcholine from domains formed with cholesterol

Abstract: In this study, we compared domain formation in raftlike mixtures of cholesterol and dioleoylphosphatidylcholine (DOPC) with either sphingomyelin (SM) or dipalmitoylphosphatidylcholine (DPPC). Using 2 H nuclear magnetic resonance, we studied the properties of the lipid enriched in the £uid phase, DOPC. We found that acyl chain 2 H-labeled DOPC is much less ordered in SM-containing mixtures than in those containing DPPC, suggesting that DOPC in the SM-containing mixture senses a lower concentration of cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
54
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 34 publications
15
54
0
Order By: Relevance
“…phatidylcholine and sphingomyelin molecules, suggesting that these microdomains are enriched in sphingomyelin and likely exist in a liquid-ordered phase. These results were in good agreement with previous AFM reports on the spontaneous formation and thickness of cholesterol-and/or sphingomyelinrich lipid microdomains in supported lipid bilayers (49,50,53). The lipid microdomains were heterogeneous in size, ranging from ϳ50 to 500 nm in diameter, a size distribution that probably reflects lateral mobility and merger of smaller microdomains during the transition from liposomes to a supported bilayer (50).…”
Section: P14-induced Membrane Fusion Is Sensitive To Donorsupporting
confidence: 92%
“…phatidylcholine and sphingomyelin molecules, suggesting that these microdomains are enriched in sphingomyelin and likely exist in a liquid-ordered phase. These results were in good agreement with previous AFM reports on the spontaneous formation and thickness of cholesterol-and/or sphingomyelinrich lipid microdomains in supported lipid bilayers (49,50,53). The lipid microdomains were heterogeneous in size, ranging from ϳ50 to 500 nm in diameter, a size distribution that probably reflects lateral mobility and merger of smaller microdomains during the transition from liposomes to a supported bilayer (50).…”
Section: P14-induced Membrane Fusion Is Sensitive To Donorsupporting
confidence: 92%
“…The small nanoscale domains previously observed with AFM by us and others (van Duyl et al, 2003) are found only when strong interactions with the support surface restrict lateral lipid mobility. However, there is growing evidence that functional microdomains in biological cells do in fact have nanoscale dimensions (Jacobson et al, 2007).…”
Section: Domain Coarsening In Ternary Membranessupporting
confidence: 57%
“…It is known from studies of free-standing membranes (Giant Unilamellar Vesicles-GUVs) that the membrane domains are 5-20 mm in diameter and circular due to line tension acting at the domain interfaces (Bagatolli, 2006). On the other hand, many studies of supported ternary membrane reveal much smaller (100-1000 nm) domains with very irregular shapes (van Duyl et al, 2003). This suggests that the membrane support may have a critical influence on the observed domains shapes.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, glycerolipids of plant DIM contain more saturated fatty acyl chains (Fig. 3B), which would contribute to the rigidity of the liquid-ordered phase of lipid rafts (42).…”
Section: Figmentioning
confidence: 99%